Chapter L'iconografia di Giovanni Colombini (1304-1367): fondatore dei gesuati - BISOGNI ARGENZIANO, RAFFAELE (Fragmentaria. Studi di storia culturale e antropologia religiosa, 2020)
This work will try to follow the development of the iconography of Blessed Giovanni Colombini from the first images handed down to us throughout the XV century. By reading the hagiographic sources, we will try to go back to when the choice of the Jesuati habit started and whether this remains unchanged over the years. The iconographic evidences will be of help to this end. The change in Colombini's social status led him to a radical change in his clothing, which, for some aspects, is very close to that of penitents. We will also try to understand what influence the decision (made towards the mid-XIV century) of Pope Urban V had on the Jesuati habit and therefore on the iconography of Giovanni Colombini, as regards the dress of the 'povari di Christo'.